Ziarah Wali dalam Tradisi Masyarakat - Ivatul Ulla; A. Halil Thahir; Hasan Basri; M. Qomarul Huda (Gunung Djati Conference Series, 2023)
The purpose of this study is to discuss the pilgrimage of saints in the traditions of the community. The research method used is a qualitative approach by applying participant observation methods, interviews and case studies. The results of the discussion found that the wali pilgrimage is one of the Islamic religious traditions that has many different meanings and motivations for Muslims. This tradition can also be a place to increase a sense of spirituality, strengthen unity and tolerance, and preserve the history and traditions of the Islamic religion. Many practices carried out by the community include: praying, visiting graves, bringing souvenirs, asking questions and reading holy books. This practice has become part of the culture of society. so as to be able to generate motivation for the community, one of which is: Increasing a sense of spirituality, receiving blessings, emulating the saints, preserving history and increasing unity and tolerance. In conclusion, the wali pilgrimage tradition is an important practice in society and has great spiritual, social, and economic impacts. However, visitors must respect local rules and regulations and pay attention to the environmental impact in maintaining the continuity of the pilgrimage pilgrimage practice.